O impulso renovador: a atuação da Missão Indígena na Escola Militar do Realengo (1919-1922) - Roesler, Rafael (2015)
The purpose of this study is to perform an analysis of the action of a group of instructors in the Military School of Realengo in the period between the years of 1919 and 1922, taking as its object the representations made by these actors, of what they allocated as Indigenous Mission. The effects of their actions were remarkable and they were felt by a whole generation of officers of the Brazilian Army, which became known as the 'generation of Realengo'. Although constantly remembered by the military historiography, the Indigenous Mission was still very little exploited in the academic work, in terms of its appearance, its performance in Military School and the involvement of some of its members in the lieutenants’ movement. In this way, the focus of the research has focused on how this group of instructors worked and in the changes caused and perceived by students as a function of this activity, both in education and in the military regime of daily Military School, educational establishment that wanted to form 'apolitical' officers and that served as a laboratory of the Army for the experience about which military education would be ideal for the training of its staff. The choice of the topic lies in the fact that the Mission had been formed by a group of young junior officers and captains of the Army, equipped with high- technicalprofessional capacity and whose psychological profile lead them to act in line with the practical teaching of a military nature, entirely in accordance with the rules and regulations of the Army, under the influence of the hard German model of instruction. As methodological tools the work of Michael Pollak, with regard to the construction of memory, and the institutionalization of certain narratives, and Maurice Halbwachs’s, regarding the relationship between collective memory and space were used. A survey carried out in the documentary archives of the Military School of Realengo, belonging to the Historical Archives of the Army, and in personal files and collections of oral history of Research and Documentation Center Contemporary History of Brazil, the Getúlio Vargas Foundation allowed the access to sources. It is concluded that the effort of the Indigenous Mission, pointing to the vocational training of the officers languages in the Brazilian Army, was not dissociated from the inclinations to act politically at the generation that passed by the School of the Realengo in the 1920s.